Drying of cenospheres recovered by the wet-based method from coal fly ash for their rational use - Kindzera, Diana; Atamanyuk, Volodymyr; Hosovskyi, Roman; Mitin, Ihor (Видавництво Львівської політехніки, 2023)
Since slag and coal fly ash (CFA) are major global pollutants produced by thermal power plants (TPPs), special attention should be paid to their rational disposal. Scanning electron microscopy (SEM) was used to study the morphology of CFA and it was suggested that the use potential of CFA is high due to the presence of a large number of cenospheres (CSs), that can be recovered mostly by wet methods for the production of the wide range of products with improved properties. However, such decisions regarding the application of the cenospheres are largely related to the problem of their drying after removal. The article is devoted to the investigation of the filtration method as less energy-consuming for the drying of cenospheres. The effect of the drying agent velocity on the mass transfer intensity has been established. The values of mass transfer coefficients have been calculated based on the thin-layer experimental data and equation . Calculated mass transfer coefficients for cenospheres have been correlated by the dimensionless expression , based on which equation has been proposed to calculate the mass transfer coefficients, which is important at the filtration drying equipment design stage.
Keywords: thermal power plant (TPP); slag; coal fly ash; ash/slag dump; ash/slag settling pond; cenospheres; utilization; filtration drying method; mass transfer coefficient